2010
DOI: 10.1007/s10681-010-0229-5
|View full text |Cite
|
Sign up to set email alerts
|

Mapping a gene conferring resistance to Wheat yellow mosaic virus in European winter wheat cultivar ‘Ibis’ (Triticum aestivum L.)

Abstract: Wheat yellow mosaic, caused by Wheat yellow mosaic virus (WYMV), is one of the most devastating soil-borne diseases of winter wheat (Triticum aestivum L.) in Japan. Yellow-striped leaves and stunted spring growth, symptomatic of WYMV infection, result in severe yield loss. A new putative WYMV resistance gene in the European wheat cultivar 'Ibis' was mapped in the cluster of microsatellite markers including Xcfd16, Xwmc41, Xcfd168 and Xwmc181 on the long arm of chromosome 2D at the distances of 2.0 cM, 4.0 cM, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…Ningmai 13 and Yangfumai 4 both had high resistance to wheat yellow mosaic virus as Ningmai 9. Ningmai 9 possessed the wheat yellow mosaic virus resistant QTL with the same allele on chromosome 2DL and 3BS as previous reports [ 17 , 18 ]. Ningmai 13 and Yangfumai 4 had the identical alleles on the chromosome regions with Ningmai 9.…”
Section: Discussionsupporting
confidence: 82%
“…Ningmai 13 and Yangfumai 4 both had high resistance to wheat yellow mosaic virus as Ningmai 9. Ningmai 9 possessed the wheat yellow mosaic virus resistant QTL with the same allele on chromosome 2DL and 3BS as previous reports [ 17 , 18 ]. Ningmai 13 and Yangfumai 4 had the identical alleles on the chromosome regions with Ningmai 9.…”
Section: Discussionsupporting
confidence: 82%
“…The best effective method to control the disease is to grow resistant wheat varieties, but there are few known resistance genes in current wheat cultivars. It has been reported that WYMV resistance in wheat is controlled by one to three genes (Qin et al, 1986) with one major gene being associated with homologous group 2 chromosome (Liu et al, 2005a;Nishio et al, 2010;Zhu et al, 2012). Furthermore, genetic analyses showed that the inheritance of this resistance is complex and influenced by many factors (Zhou et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, resistant genes against wheat yellow mosaic virus and soil-borne wheat mosaic virus were found on chromosomes 2D and 5D, respectively. 6 , 42 For the fine mapping of these agronomically important genes or QTLs, the number of markers must be increased around the regions of interest. From the polymorphism survey using six varieties, around 6,000 polymorphic sites were detected on the D genome, and some sites have been successfully used to develop markers (data not shown).…”
Section: Discussionmentioning
confidence: 99%